Nature of teleworking in key sectors: case studies of financial, media and software sectors in Mumbai - Aundhkar, Advait et al. (2000)
A detailed case study of the prevalence of teleworking in three sectors - software, financial and banking, and media - reveals that the current regulatory mechanism operating in the information technology industry and the inadequate infrastructural services are major hurdles in the growth of teleworking and teletrade. - Reproduced
Keywords: Telecommunications - India - Maharashtra; Case studies; Computer software - India - Maharashtra; Information technology; Telework